Elementary School Students Learning Experince: Through Padlet and Quizwhizzer Media in the Exploration and Reinforcement Stages - Kharisma Salsabila, Chika; Eucarista, Azilla Irmadhea; Wibawa, Priscilla Regina Pramesti (Indo-MathEdu Intellectuals Journal, 2026)
The development of digital technology has brought significant changes to learning practices in elementary schools, particularly in the use of digital learning media. The purpose of this study is to describe students' learning experiences in elementary school using Padlet and QuizWhizzer media during the exploration and reinforcement stages of material about Pancasila symbols. The research method used is a qualitative approach with a descriptive design. Elementary school students are the subjects of this research. Data collection was carried out through the stages of observation, semi-structured interviews, and documentation. To ensure the validity of the research data, data analysis was conducted through the stages of data reduction and data presentation. The research results indicate that the Padlet platform has the ability to encourage students to actively participate in exploring the material. Meanwhile, QuizWhizzer serves as a medium for reinforcing material, helping students become more motivated to learn, more focused, and better understand the concepts taught through game-based quiz learning. Interactive, meaningful, and student-centered learning experiences can be achieved using the Padlet and QuizWhizzer platforms. The results of this study demonstrate the relevance of how important it is to use digital media for learning that aligns with 21st-century education.